How do different delivery schedules of tailored web-based physical activity advice for breast cancer survivors influence intervention use and efficacy? - Short, C.; Rebar, Amanda; James, E.; Duncan, M.; Courneya, K.; Plotnikoff, R.; Crutzen, R.; Vandelanotte, C. (Springer New York LLC, 2017)
© 2016, Springer Science+Business Media New York. Purpose: The purpose of the study is to investigate the impact of differing delivery schedules of computer-tailored physical activity modules on engagement and physical activity behaviour change in a web-based intervention targeting breast cancer survivors. Methods: Insufficiently active breast cancer survivors (n = 492) were randomly assigned to receive one of the following intervention schedules over 12 weeks: a three-module intervention delivered monthly, a three-module intervention delivered weekly or a single module intervention. Engagement with the website (number of logins, time on site, modules viewed, action plans completed) was measured using tracking software. Other outcomes (website acceptability, physical activity behaviour) were assessed using online surveys. Physical activity outcomes were analysed using regression models for both study completers and when applying intention-to-treat (using multiple imputation). Results: Completers allocated to the monthly module group rated the intervention higher (b = 2.2 95 % CI = 0.02–4.53) on acceptability and had higher levels of resistance-training (IRR = 1.88, 95 % CI = 1.16–3.04) than those in the single module group. When accounting for missing data, these differences were no longer significant. The completion of at least two action plans was higher among those allocated to the monthly module group compared to those in the weekly module group (53 vs 40 %, p = 0.02); though the completion of at least two modules was higher in the weekly module group compared to the monthly module group (60 vs 46 %; p = 0.01). There were no other significant between group differences observed. Conclusion: This study provides preliminary evidence that web-based computer-tailored interventions can be used to increase physical activity among breast cancer survivors. Further, there were some outcome differences based on how the tailored modules were delivered, with the most favourable outcomes observed in the monthly delivery group. Implications for Cancer Survivors: This study will be useful for informing the design of future web-based interventions targeting breast cancer survivors.